Geometry Learning Strategy at MTs Negeri 1 Sinjai - Fetti Fatricia Amdar; Sri Jingga Anggriani Putri; Nurazizah; Irmayanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Geometry learning plays a role in the development of students' spatial and visual understanding. Through geometry, students learn to recognize, understand, and manipulate geometric objects in three dimensions. Effective teaching strategies in learning geometry include a problem-based approach, the use of manipulative aids, and the application of technology. The purpose of this study was to describe the strategies used by teachers at MTs Negeri 1 Sinjai in teaching geometry. The type of research used is descriptive with a qualitative approach. The research subjects were Mathematics teachers at MTs Negeri 1 Sinjai who had taught the material using a purposive sampling technique. The instrument used is an interview sheet. The data collection technique used was interviews to find out in depth about the strategies used by MTs Negeri 1 Sinjai teachers in learning geometry. Data analysis used is data collection, data reduction, data presentation and conclusion drawing. The results of this study stated that the mathematics teacher at MTs Negeri 1 Sinjai used the discovery learning method (guided discovery), conducted group discussions, used picture media, used student worksheets (LKPD), textbooks and power points. In this digital era, it is recommended that teachers introduce the GeoGebra application in learning geometry.